Discursive Citizenship: The Body Politic in Cyberspace - Kolko, Beth (International Journal of Virtual Reality, 2001)
Questions of community and identity dominate discussions of cyberspace. Recent work in a variety of disciplines points to a fluidity of identity within virtual environments that is both a determining factor in how the space is used and also a way to begin theorizing the possibilities of the space. Mark Poster, Sherry Turkle, Alluecquere Stone, Lisa Nakamura, and Jennifer Mnookin are a few of the scholars who have provided wide-ranging analyses that resonate with one another in their portrayals of dispersed and fragmented presences in virtual communities. These questions of identity have variously raised issues relating to the body, and much current research on cyberspace addresses the ways in which the material is implicated in the virtual. This paper explores how discursive formations of identity affect community development in virtual environments, primarily with regard to experiments in governance within online communities. In particular, the paper examines how the collaborative nature of cyberspace complicates effective use of virtual environments for complex community functions. While focusing on rhetorical theory, the paper argues that traditional relations between speaker and audience are blurred substantially in cyberspace, sufficiently so that attempts at establishing a kind of communicative ethics online are difficult at best. The premise that cyberspace communities, in particular MUDs (multiuser domains) and MOOs (multiuser object oriented environments), are writing environments wherein discursive negotiation plays a major role in community formation frames the analysis of the rhetorical function of place. Although new media, and increased bandwidth, are expanding the kinds of sign systems that are used to communicate in cyberspace, the claim to identity online is still very much a matter of discursive choice.